Experimental studies of the effects of grazing by captive goslings of the lesser snow goose on the vegetation of a subarctic salt marsh. - Hik, David S. (1988)
Masters Thesis completed in 1988 by D. S. Hik at the University of Toronto. Supervised by Dr. R.L. Jefferies. SUMMARY: 1.The effects of grazing by captive goslings of the Lesser Snow Goose on the vegetation of La Pérouse Bay salt marsh were investigated. Goslings fed on swards of Puccinellia phryganodes; net above-ground primary production (NAPP)and forage quality (amounts of nitrogen and carbon) were measured over the course of the season. 2.Grazing early in the season resulted in increased NAPP of swards of Puccinellia, as predicted by the herbivore-optimization model. The greatest enhancement of production occurred at low to moderate levels of grazing compared to production in ungrazed swards. At higher levels of grazing production was reduced. Enhancement of NAPP following grazing was detected only early in the season; the ability of the plants to recover from the effects of grazing decreased later in the season. 3.Repeated grazing episodes on the same swards of Puccinellia over the course of the summer demonstrated that swards could maintain high rates of production, and high nitrogen content of shoots even when they were grazed late into the season. Swards of Puccinellia grazed at approximately 24 day intervals throughout the summer and swards grazed at approcimately 12 day intervals on four occasions had the largest increase in NAPP compared to ungrazed swards. Increases in NAPP were achieved over a wide range of grazing periods and intervals between grazing episodes. 4. NAPP was 30 to 40% less in swards of Puccinellia where faeces were removed compared to corresponding values for swards where the faeces remained. Faeces provided a source of soluble nitrogen that could be readily taken up by plants. However, the amount nitrogen contributed by the feaces to the total amount of nitrogen accumulated in the above-ground biomass of grazed swards of Puccinellia was less than 10%. Up to 44% of total nitrogen accumulated in the above-ground biomass of grazed swards could not be accounted for. 5. ...